2002
DOI: 10.1071/rd01112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the immunocontraceptive effect of a zona pellucida 3 peptide antigen in wild mice

Abstract: Immunizing laboratory mice against a short peptide to mouse zona pellucida protein 3 (mZP3; amino acids 328-342) reduces fertility in some strains. This antigen was therefore tested to see if it is suitable for use in an immunocontraceptive vaccine to control wild mice. Mouse zona pellucida protein 3 peptide conjugated to a carrier protein (keyhole limpet hemocyanin) was considerably more immunogenic and effective in reducing fertility in wild mice when compared with inbred BALB/c mice. Fertility of the immuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In several studies, high titers of ZP-specific total IgG Abs are associated with infertility in mice immunized with the recombinant ZP3 protein or ZP3 peptides (12,18,39). Consistent with those studies, we also demonstrated that the higher level of total IgG Abs was correlated with infertility in mice in the group co-immunized with chi-(pcD- Lzp3 +pcD- mIL-33 ) (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, high titers of ZP-specific total IgG Abs are associated with infertility in mice immunized with the recombinant ZP3 protein or ZP3 peptides (12,18,39). Consistent with those studies, we also demonstrated that the higher level of total IgG Abs was correlated with infertility in mice in the group co-immunized with chi-(pcD- Lzp3 +pcD- mIL-33 ) (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…One interesting application has been for reproductive control by immunizing animals against sex hormones, gametes or other key targets in the reproductive tract [Figure 1]. [3842] The most studied reproductive hormone as a vaccine target is luteinizing hormone releasing hormone (LHRH), also known as gonadotrophin-releasing hormone (GnRH). [43–52] GnRH is a small 10 amino acid peptide released from the hypothalamus in all species of mammals and has a central regulatory role in reproductive functions.…”
Section: Types Of Animal Vaccinesmentioning
confidence: 99%
“…Strategies to control fertility using vaccines based on gamete antigens, particularly zona pellucida proteins, have been the most widely researched. [912425355] However, commercial successes for immunocontraceptive vaccines have been relatively few primarily because of poor immunogenicity of small peptide self antigens and difficulties in cost-effective practical delivery of the vaccines to target wildlife species. Another interesting evolution which took place with the use of acellular antigens is development of combined vaccines incorporating two or more antigens, initially used for humans and which later paved the way for numerous combined veterinary vaccines.…”
Section: Types Of Animal Vaccinesmentioning
confidence: 99%
“…These include male-fertility-associated antigens, such as PH20, FA-1 and SP-10 (Suri 2004), and female-fertility-associated antigens, such as ZP1, ZP2 and ZP3 (Paterson et al 2000;Mackenzie et al 2006). Small peptides or linear arrays of peptides (polyepitopes) have also been trialled as immunocontraceptives (Miller et al 1997;Hardy et al 2002aHardy et al , 2002b. Of the sex-specific antigens, male antigens have proven less successful than female-fertility antigens, of which the most effective has been the zona antigen, ZP3.…”
Section: Alternative Antigen Targetsmentioning
confidence: 99%